2021
DOI: 10.1038/s41598-021-89250-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of grain boundaries as percolation pathways in quartz-rich continental crust using Atomic Force Microscopy

Abstract: Hydrous fluids play a vital role in the chemical and rheological evolution of ductile, quartz-bearing continental crust, where fluid percolation pathways are controlled by grain boundary domains. In this study, widths of grain boundary domains in seven quartzite samples metamorphosed under varying crustal conditions were investigated using Atomic Force Microscopy (AFM) which allows comparatively easy, high magnification imaging and precise width measurements. It is observed that dynamic recrystallization at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…EBSD analyses of these samples were performed at the Central Research Facility of the Indian Institute of Technology, Kharagpur. The EBSD system consists of a Zeiss-Auriga Compact field emission gun-scanning electron microscope (FEG-SEM) fitted with a Gemini column Schottky type field emission filament along with an Oxford Nordlys detector for EBSD pattern detection (see Dobe et al 2021). Indexing of electron backscatter patterns was carried out using an AZtec HKL from Oxford Instruments.…”
Section: Methodsmentioning
confidence: 99%
“…EBSD analyses of these samples were performed at the Central Research Facility of the Indian Institute of Technology, Kharagpur. The EBSD system consists of a Zeiss-Auriga Compact field emission gun-scanning electron microscope (FEG-SEM) fitted with a Gemini column Schottky type field emission filament along with an Oxford Nordlys detector for EBSD pattern detection (see Dobe et al 2021). Indexing of electron backscatter patterns was carried out using an AZtec HKL from Oxford Instruments.…”
Section: Methodsmentioning
confidence: 99%
“…Connolly & Podladchikov, 2004). Recent studies have demonstrated that viscous flow can produce porosity in deforming rocks through dynamic recrystallization (Gilgannon et al 2020) and creep cavitation processes (Fusseis et al 2009;Menegon et al 2015;Précigout et al 2019;Dobe et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Information was getting via the AFM method dimensional images of the surface topography of the granules and the distribution of cumulating granularity for the zinc oxide NPs [33].…”
mentioning
confidence: 99%